1994
DOI: 10.1111/j.1365-2249.1994.tb06082.x
|View full text |Cite
|
Sign up to set email alerts
|

IgE elevation and IgE anti-malarial antibodies in Plasmodium falciparum malaria; association of high IgE levels with cerebral malaria

Abstract: SUMMARYIn the course of studying immunoregulation in human Plasmodium falciparum malaria we have investigated IgE levels and IgE anti-plasmodial antibodies in children and adults from areas of high malaria endeniicity in both Africa and Asia. On average, 85% of all donors had significantly elevated levels of total IgE. A fraction of the IgE had anti-plasmodial activity as revealed by ELISA with lysates of infected crythrocytes as antigen. Using synthetic peptides representing antigenic regions of two major pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
2
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(61 citation statements)
references
References 49 publications
2
56
2
1
Order By: Relevance
“…IgE antibodies may protect against, or participate in, the pathogenesis of malaria. The association of high anti-P. falciparum IgE levels with a reduced risk of developing clinical malaria suggests a protective role [13], whereas the observation that circulating levels of IgE most often correlate with severe rather than uncomplicated disease suggests a pathogenic role [14]. Recently, Duarte et al [15] have reported that circulating levels of total IgE do not appear to correlate with protection or pathology during malaria.…”
Section: Discussionmentioning
confidence: 99%
“…IgE antibodies may protect against, or participate in, the pathogenesis of malaria. The association of high anti-P. falciparum IgE levels with a reduced risk of developing clinical malaria suggests a protective role [13], whereas the observation that circulating levels of IgE most often correlate with severe rather than uncomplicated disease suggests a pathogenic role [14]. Recently, Duarte et al [15] have reported that circulating levels of total IgE do not appear to correlate with protection or pathology during malaria.…”
Section: Discussionmentioning
confidence: 99%
“…These IgE antibodies are produced from the Th-2 immune response and have been used in serodiagnosis and also as indicator of the disease activity in many diseases such as toxoplasmosis, cerebral malaria, and visceral leishmaniasis (Wong et al 1993;Perlmann et al 1994;Atta et al 1998).…”
Section: Anti Leishmanial Ige Antibodymentioning
confidence: 99%
“…In addition, with repeated exposure to Plasmodium spp., an immune response repertoire, chiefl y consisting of cytophilic IgG1 and IgG3 subclasses, but also IgE, will progressively evolve in children, having the capacity to control and reduce parasite multiplication [9,[20][21][22]. Such responses may gradually approach, and come to resemble, the immune reactivity profi les observed in adults, where antibodies specifi c against multiple P. falciparum antigens mediate partial parasite control [23].…”
Section: Introductionmentioning
confidence: 99%
“…The initial fi nding indicated that IgE elevation was most pronounced in sera from patients with cerebral malaria [22]. Later observations suggested that IgE may be considered a pathogenic factor in severe disease without cerebral involvement and, probably, in P. falciparum malaria in general [24].…”
Section: Introductionmentioning
confidence: 99%